2019
DOI: 10.1002/ajhb.23274
|View full text |Cite
|
Sign up to set email alerts
|

Associations between adiposity measures and 25‐hydroxyvitamin D among police officers

Abstract: Objective: Studies show that serum levels of 25-hydroxyvitamin D (25(OH)D), a biomarker for vitamin D status, are lower in persons with higher adiposity levels and that police officers have been found to have a high prevalence of obesity. The purpose of this study was to examine relationships between several adiposity measures and 25(OH)D, and also compare those measures to determine the best one that predicts insufficiency of 25(OH)D (<20 ng/mL) among police officers in the Northeast area of the United States… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
4
1
1
Order By: Relevance
“…This finding is in contrast to research from Quebec, Canada where 21.1% of male and only 7.3% of female police officers were obese according to BMI [23]. Additionally, research from New York, USA, found 50.7% of male and only 21.3% of female police officers were obese according to BMI [10]. It may be that additional lifestyle factors not measured in our study accounted for the different prevalence rates by sex [8].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This finding is in contrast to research from Quebec, Canada where 21.1% of male and only 7.3% of female police officers were obese according to BMI [23]. Additionally, research from New York, USA, found 50.7% of male and only 21.3% of female police officers were obese according to BMI [10]. It may be that additional lifestyle factors not measured in our study accounted for the different prevalence rates by sex [8].…”
Section: Discussioncontrasting
confidence: 99%
“…As there are multiple ways to measure obesity, waist circumference (WC) is a recommended measure of central adiposity (i.e., excess fat tissue) to help indicate increased cardiovascular disease risk [9]. WC has been compared to both BMI and BF% among US police officers [10], female firefighters [11], and military personnel [12], as well as Russian firefighters [13]. All three measures (i.e., BMI, BF%, and WC) have been highly correlated in US police officers [10].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between vitamin D and anthropometric parameters in the setting of HF has not been thoroughly explored. In the general population, there seems to be a consensus of a negative correlation between serum 25(OH)D concentrations and BMI, WC, and BF% [33,61,62,63,64], mainly attributed to sequestration of vitamin D by adipocytes. However, controversy has been found in patients with HF, as no correlation has been reported in this context between serum 25(OH)D levels and body weight, BMI, mid-arm muscle circumference [65], arm lean mass, leg lean mass, and grip strength (rather related to muscle mass and strength) [66].…”
Section: Discussionmentioning
confidence: 99%
“…These findings can be attributed to the higher concentration of body fat in women, influenced by the increase in age (Tanwi et al, 2019), parity (LisowskI et al, 2019, and the action of female hormones (Suliga et al, 2016). In addition, one study found that % body fat seems to be a better predictor of lower 25(OH)D concentrations, regardless of gender (Gu et al, 2019). Several studies have observed an association between the HTW phenotype and metabolic changes (Ding et al, 2019;Muñoz-Garach et al, 2019;Ren et al, 2016).…”
Section: Discussionmentioning
confidence: 99%